Tren Pembelajaran Konsep Mengapung dan Tenggelam di Sekolah Dasar: A Systematic Literature Review - Salsa Rutanti; Nurul Deviyanti; Afridha Laily Alindra (STKIP Subang, 2026)
The concepts of floating and sinking are among the science topics in elementary schools that often lead to students’ misconceptions because they are closely related to the understanding of density and buoyancy concepts. This study aims to analyze trends in learning methods used for teaching floating and sinking concepts in elementary schools and to examine their effectiveness in improving students’ conceptual understanding. This study employed a Systematic Literature Review (SLR) method using the PRISMA approach through the analysis of scientific articles published between 2015 and 2025 obtained from Google Scholar and Scopus databases. Based on the identification, screening, and selection process, 10 relevant articles related to science learning in elementary schools were selected. The findings indicate that hands-on experiments and inquiry learning are the most dominant and effective learning methods in enhancing students’ understanding of floating and sinking concepts. In addition, various innovative approaches such as STEAM, ethnoscience-based learning, haptic simulation, density-based learning, and instructional media also contribute to improving critical thinking skills, creativity, observational abilities, and reducing students’ misconceptions. Therefore, learning about floating and sinking concepts will be more effective when supported by active learning methods, direct experiences, innovative media, and contextual approaches aligned with elementary school students’ characteristics.